Herbal product use patterns and possible herb-drug interactions among older adults in Turkey - KARAALP, ATİLA (ELSEVIER GMBH, 2021)
Background: Traditional and Complementary medicine use is on the increase universally. In this descriptive study, the aim is to evaluate the frequency and determinants of herbal product use, as well as determine possible drug-herb interactions among older individuals who live in rural and urban areas. Methods: The study was carried out with individuals 65 years or older in one urban and five rural neighborhoods in Bursa, Turkey. The data was collected during face-to-face interviews using a questionnaire comprising 43 questions. The participants were asked about the drugs and herb/herbal products they use and then the possible drug-herb interactions were evaluated using Micromedex (R). Results: Among the participants, 82.2 % reported using at least one drug regularly, and 18.3 % used at least one herb/herbal product in the past year (rural 26.1 %, urban 13.4 %). Most commonly used herb/herbal products were plane tree leaves and black cumin. Herbal product use was seen more among those experiencing difficulties accessing health care and living alone. Among those using drug and herb/herbal products concurrently, the possible drug-herb interaction rate was 7.5 %. Conclusions: Physicians providing health care services to geriatric populations should inquire about usage of drugs and herbs. Conventional medicine should be made accessible to every older adult, and it should be ensured that they do not have to resort to complementary therapies that could harm their health.
Keywords: Herb-drug interactions; Geriatrics; Complementary therapies; SUPPLEMENT USE; ALTERNATIVE MEDICINE; COMPLEMENTARY; PREVALENCE; THERAPIES; DIETARY; CARE; METAANALYSIS; PREDICTORS; ACCESS